Prevalence of Candida albicans in the oral cavity of Beta Thalassemia Major and Thalassemia Minor Patients [version 2; peer review: 2 approved] - Maha Adel Mahmood; Saba Sami Abd Al Wahab (F1000Research)
Aims To examine the correlation between iron, ferritin concentrations, and C. albicans infection in individuals with beta-thalassemia major and beta-thalassemia minor compared with healthy subjects. Materials and methods It involved 90 participants, thirty patients with thalassemia major and thirty patients with thalassemia minor compared with thirty healthy controls. Saliva samples were obtained and cultivated to isolate, identify, and calculate the viable colony count of C. albicans in (cfu/ml). In contrast, serum levels of iron and ferritin were quantified using chemical analyzers. Result Showed that 73.33% of thalassemia major group exhibited oral C. albicans colonization, which is significantly higher than that of thalassemia minor group 40% and control group 6.67%. Biochemical analyses revealed significantly higher iron 278.82 μg/dl and ferritin 2783.80 ng/ml levels in major group p<0.001 when compared with both thalassemia minor group 122.652 μg/dl, 74.723 ng/ml and control groups 127.438 μg/dl and 63.150 ng/ml respectively. C. albicans colony count in saliva was significantly elevated in beta-thalassemia major, as compared with beta-thalassemia minor group and control group. Conclusion Findings suggest that iron overload, which results from recurrent blood transfusions and causes immune dysfunction, contributes to higher risk of oral fungal infections in Beta-thalassemia patients compared with controls.